Self-citations in musculoskeletal radiology: frequency and pattern analysis. (November 2019) - Dessouky, Riham; Zhang, Lihua; Wadhwa, Vibhor; Xi, Yin; Chhabra, Avneesh
Background: Author self-citation can affect quantitative aspects of scientific research. However, little is known about its prevalence in radiology literature. Purpose: The aim of this study was to determine the frequency and factors associated with author self-citation in musculoskeletal radiology. Material and Methods: Retrospective review of bibliographic data in musculoskeletal radiology articles of two separate journals over a 23-month period (January 2015 to November 2016) was performed to determine frequency of author self-citations. Other data included article type, topic, title length, author order, affiliation, and geographic location. Results: One-third of all included articles had author self-citations with a mean and median of 2.8 and 2 citations per article. Case reports contained up to 52.4% self-citations (mean = 11.2%, 95% CI = 5.9–16.5). Larger frequencies of self-citations were found among first and second authors and university-affiliated authors. The United States was the most frequent country to produce publications but did not have the highest percentage of self-citations. Conclusion: Self-citations in musculoskeletal radiology is no different than other medical fields. It does not currently seem to pose a threat on the integrity of scientific research and is usually needed to expand on previous knowledge. Nevertheless, authors and journals should be aware of implications of abusing such practice on future medical research.